Performance enhancement of an antenna using low temperature co-fired ceramic (LTCC) for Wi-Fi applications / Nor Ashidah Mat Nor - Mat Nor, Nor Ashidah (2014)
This paper presents the design of performances enhancement of an antenna using Low Temperature Co-fired Ceramic {LTCC) multilayer packaging technology with frequency of 2.4GHz for wireless communication (Wi-Fi) application using Computer Simulation Tool (CST). The LTCC antenna of 8 layers substrate is designed on the substrate type of Ferro A6S (lossy) with dielectric constant of 5.9, substrate thickness of 0.096mm and silver thickness of 0.01mm respectively. The parameters of the antenna need to be optimized in order to achieve better performances. The simulation results of return loss (S11), gain, directivity, bandwidth and Voltage Standing Wave Ratio (VSWR) are compared and analyzed between single element patch . antenna, 1 x2 planar array antenna, 2x2 planar array antenna and 2x2 planar array antenna with Defected Ground Structure (DGS). The performance of single element L TCC antenna gain increment by 65%. The gain has increased up to 3.43dB which is from 5.268dB to 8.698dB. In other hand, the directivity also increased by 3.333dB which is from 6.471dBi to 9.804dBi and denotes by 52%. All the designed LTCC antennas have return loss below than -1 0dB with VSWR approximately equal to 1.0.